Treatment of microglia with Anti-PrP monoclonal antibodies induces neuronal apoptosis in vitro. Issue 12 (December 2021) - Adhikari, Utpal Kumar; Sakiz, Elif; Habiba, Umma; Mikhael, Meena; Senesi, Matteo; David, Monique Antoinette; Guillemin, Gilles J.; Ooi, Lezanne; Karl, Tim; Collins, Steven; Tayebi, Mourad
Abstract: Previous reports highlighted the neurotoxic effects caused by some motif-specific anti-PrP C antibodies in vivo and in vitro . In the current study, we investigated the detailed alterations of the proteome with liquid chromatography–mass spectrometry following direct application of anti-PrP C antibodies on mouse neuroblastoma cells (N2a) and mouse primary neuronal (MPN) cells or by cross-linking microglial PrP C with anti-PrP C antibodies prior to co-culture with the N2a/MPN cells. Here, we identified 4 (3 upregulated and 1 downregulated) and 17 (11 upregulated and 6 downregulated) neuronal apoptosis-related proteins following treatment of the N2a and N11 cell lines respectively when compared with untreated cells. In contrast, we identified 1 (upregulated) and 4 (2 upregulated and 2 downregulated) neuronal apoptosis-related proteins following treatment of MPN cells and N11 when compared with untreated cells. Furthermore, we also identified 3 (2 upregulated and 1 downregulated) and 2 (1 upregulated and 1 downregulated) neuronal apoptosis-related related proteins following treatment of MPN cells and N11 when compared to treatment with an anti-PrP antibody that lacks binding specificity for mouse PrP. The apoptotic effect of the anti-PrP antibodies was confirmed with flow cytometry following labelling of Annexin V-FITC. The toxic effects of the anti-PrP antibodies was more intense when antibody-treated N11 were co-cultured with the N2a and the identified apoptosis proteome was shown to be part of the PrP C -interactome. Our observations provide a new insight into the prominent role played by microglia in causing neurotoxic effects following treatment with anti-PrP C antibodies and might be relevant to explain the antibody mediated toxicity observed in other related neurodegenerative diseases such as Alzheimer. Highlights: Antibody cross-linking neuronal PrPC induces apoptosis. Antibody cross-linking microglial PrPC induces neuronal apoptosis. Different apoptotic pathways were triggered by specific anti-PrP antibody treatments. Abstract : Anti-PrP antibodies; Apoptosis; Cellular prion protein; Microglia; Neuroblastoma cell line (N2a); Microglia cell line (N11); Primary neuronal cells.